Design Grafis di Era Digital : Pengenalan dan Pemanfaatan - Anita Herlinda Siregar; Bob Zimazanya; Alicia; Siti Nurjanah; Rachel Martina Etikasari Sandehang (PT Jurnal Cendekia Indonesia, 2025)
With the development of digital technology, the way people interact, work, and create has changed. Because of the ability to convey messages visually effectively, graphic design is one of the essential skills in the digital era. Unfortunately, not all groups of people understand or have access to this skill. The purpose of this community service event is to introduce the basics of graphic design and how to use it in the digital era to the general public, especially young people at Taman Baca Perigi, Depok. A hands-on, interactive, and participatory training approach was used to carry out the activity on May 4, 2025. Some of the materials taught included design concepts and basics, an introduction to web-based design tools such as Canva, and a simple content design practice session. The results of the activity showed that participants better understood the concept of graphic design and were better able to use their own design applications. In addition, participants realized how important design is to support education, campaigns, and digital communication. This training also encouraged participants' interest in the world of visual design. It is hoped that this activity will improve the visual literacy of the community and provide opportunities for designers to utilize their abilities to face digital challenges in the future.